Generating the Specialized Engineering Word List for Students at Tertiary Level Education - Zuraina, Ali; Hafizoah, Kassim; Nurul Nadia, Mohammad; Rosnani, Ismail; Siti Norzaimalina, Abd Majid; Mohd Amir Izuddin, Mohamad Ghazali (AENSI Publishing, 2014)
Research findings provide evidence that the use of word list may assist students in learning selected words which they may need to know for the purpose of reading and understanding a technical text. Objective: The objectives of the paper are to determine the specialised engineering word contained in the engineering textbooks as well as to identify the percentage of words contain in Specialised Engineering Word List (SEWL) as it is compared to AWL. Results: This study has found that there are 66 words in SEWL and less than 20% of the words listed in SEWL are available in AWL. Conclusion: The findings enhance our understanding that developing a specialised word list requires a systematic process. And the use of corpora instead of dictionary is more appropriate for researchers attempting to generate a word list.